2011
DOI: 10.1038/ki.2011.151
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioral therapy for sleep disturbance decreases inflammatory cytokines and oxidative stress in hemodialysis patients

Abstract: Sleep disturbance is common in dialysis patients and is associated with the development of enhanced inflammatory responses. Cognitive-behavioral therapy is effective for sleep disturbance and reduces inflammation experienced by peritoneal dialysis patients; however, this has not been studied in hemodialysis patients. To determine whether alleviation of sleep disturbance in hemodialysis patients also leads to less inflammation, we conducted a randomized controlled interventional study of 72 sleep-disturbed hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 43 publications
1
107
1
Order By: Relevance
“…The drop-out rate (70%) was higher than the previously reported findings of between 7% and 11% in the ESKD population [4,20]. Most participants left the study during the initial phase when CBT was the only form of intervention.…”
Section: Discussioncontrasting
confidence: 49%
“…The drop-out rate (70%) was higher than the previously reported findings of between 7% and 11% in the ESKD population [4,20]. Most participants left the study during the initial phase when CBT was the only form of intervention.…”
Section: Discussioncontrasting
confidence: 49%
“…In a recent study, poor sleep quality was directly associated with higher fatigue severity, and also mediated the association between lower mood and fatigue severity in RA (Rongen‐van Dartel et al ., 2016). In fact, trials of CBT interventions aimed at sleep quality in dialysis patients found significant improvements in fatigue (Chen et al ., 2008, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Duarte et al (2009) demonstrated that CBT performed during 3-month-long group therapy is effective for improving depression and many dimensions of QoL in chronic HD patients. Chen et al (2011) conducted a randomized controlled interventional study of 72 sleep-disturbed HD patients. Compared with the control group (who received sleep health education), patients who received CBT had significant improvements in sleep quality, fatigue, depression, and anxiety.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%